COMPARISON OF â€œKAMPONGâ€ AND COMMERCIAL CHICKEN EGG-BASED EXTENDERS ON CRYOPRESERVED GOAT SPERM MOVEMENT CHARACTERISTICS - C.W.K., Janice,; K.D.S, Kanwal,; W.E., Wan Khadijah,; R.B., Abdullah, (Malaysian Journal of Science, 2013)
Replacement of egg yolk obtained from commercial chicken with that of kampong chicken egg in the commonly used semen extender, TRIS, was investigated on cryopreserved goat spermatozoa movement characteristics. Fresh and frozen-thawed sperm movement characteristics such as progressive motility, progressive velocity and linearity were analyzed using computer assisted semen analyzer. Sperm samples in the experimental group showed apparently better sperm movement characteristics compared to those cryopreserved in commercial chicken egg yolk, however these differences were non-significant. Based on this preliminary study it could be concluded that kampong egg yolk offers an alternative choice in freezing protocol of goat spermatozoa for artificial insemination. (Keywords: Kampong egg yolk, Semen extender, Computer-assisted sperm analysis, Goat sperm movement characteristics)